Micromorphological Characterization and DNA Barcoding of Durio macrantha Kosterm. from the Bogor Botanical Garden Collection - Magandhi, Mahat; Rusydina, Diyana Sabila; Mukaromah, Arnia Sari (Buitenzorg: Journal of Tropical Science, 2025)
Durio macrantha is an endemic species first discovered in 1981 in Gunung Leuser National Park, North Sumatra, and has been conserved at the Bogor Botanical Garden since 1994. This study aims to characterize the micromorphology and DNA profile D. macrantha using DNA barcoding with rbcL and ITS gene markers. Sample of D. macrantha were collected from the Bogor Botanical Gardens for analysis. Micromorphological analysis revealed that the leaves exhibit three vein types (primary, secondary, and tertiary) with a pentagonal venation pattern and a tri-veinlet veinlet pattern. Additionally, eight types of trichomes were observed on the abaxial surface. Molecular characterization showed that the rbcL sequence was 563 bp long, with nucleotide composition T (27.9%), C (21.7%), A (27.9%), and G (22.6%). The ITS sequence was 960 bp long, with nucleotide composition T (15.4%), C (33.4%), A (19.0%), and G (32.2%). BLAST analysis of both rbcL and ITS genes revealed a high level of similarity between D. macrantha and D. zibethinus. This study provides fundamental data supporting the conservation and further research of D. macrantha, particularly in morphological and molecular aspects.